2021
DOI: 10.3390/biomedicines9020221
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Diseases and Down Syndrome: How Are They Linked Together?

Abstract: Down syndrome is a genetic disorder caused by the presence of a third copy of chromosome 21, associated with intellectual disabilities. Down syndrome is associated with anomalies of both the nervous and endocrine systems. Over the past decades, dramatic advances in Down syndrome research and treatment have helped to extend the life expectancy of these patients. Improved life expectancy is obviously a positive outcome, but it is accompanied with the need to address previously overlooked complications and comorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 166 publications
0
24
0
Order By: Relevance
“…Trisomy 21 is also associated with defective neutrophil and monocyte chemotaxis and phagocytosis [9,10], plus T system immune-deficiencies [11] and premature immune system senescence [12]. These conditions predispose DS subjects to chronic proinflammatory status and increase in oxidative stress due to mitochondrial dysfunction which, concomitant to metabolic diseases such as diabetes [13], are also responsible for higher susceptibility to oral and extra-oral infection, than in euploid and immunocompetent subjects.…”
Section: Introduction 1down Syndromementioning
confidence: 99%
“…Trisomy 21 is also associated with defective neutrophil and monocyte chemotaxis and phagocytosis [9,10], plus T system immune-deficiencies [11] and premature immune system senescence [12]. These conditions predispose DS subjects to chronic proinflammatory status and increase in oxidative stress due to mitochondrial dysfunction which, concomitant to metabolic diseases such as diabetes [13], are also responsible for higher susceptibility to oral and extra-oral infection, than in euploid and immunocompetent subjects.…”
Section: Introduction 1down Syndromementioning
confidence: 99%
“…Similar to the population of healthy people, obese patients were expected to have a higher content of lean body mass than normal-weight children. The world of science draws attention to problems that may interfere with the proper quality/quantity of muscle mass in children with DS highlighting mainly a lack of physical activity [16,17]. Pitchford et al showed that obesity in children with DS negatively correlated with their daily physical activity [18].…”
Section: Discussionmentioning
confidence: 99%
“…The muscle mass may also be affected by insulin resistance and inflammation associated with adiposity [19]. Abdominal obesity leads to increased circulating fatty acids, associated inflammation, and ectopic triglyceride storage (in muscle and organs) [17].…”
Section: Discussionmentioning
confidence: 99%
“…This adult population suffers from complications in addition to those already presented in the pediatric period (facial changes, malformed limbs, affected skin and muscles, atrioventricular abnormalities, and higher incidence of leukemia, among others) 3 . As these individuals age, they may present more immunological and metabolic disorders, with obesity and dyslipidemia being prevalent, 4 as well as early senile dementia and neurodegenerative processes 5 . In addition to systemic complications, patients with DS present with oral complications and diseases, such as periodontal disease 6…”
Section: Introductionmentioning
confidence: 99%
“…As these individuals age, they may present more immunological and metabolic disorders, with obesity and dyslipidemia being prevalent, 4 as well as early senile dementia and neurodegenerative processes. 5 In addition to systemic complications, patients with DS present with oral complications and diseases, such as periodontal disease.…”
mentioning
confidence: 99%